2020
DOI: 10.3389/fchem.2019.00912
|View full text |Cite
|
Sign up to set email alerts
|

Operando Studies of the Electrochemical Dissolution of Silver Nanoparticles in Nitrate Solutions Observed With Hyperspectral Dark-Field Microscopy

Abstract: Since nanoparticles are frequently used in commercial applications, there is a huge demand to obtain deeper insights into processes at the nanoscale. Especially, catalysis, chemical and electrochemical reaction dynamics are still poorly understood. Thus, simultaneous and coupled opto-and spectro-electrochemical dark-field microscopy is used to study in situ and operando the electrochemically driven dissolution mechanism of single silver nanoparticles in the presence of nitrate ions as non-complexing counter-io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Dark-field microscopy is also frequently coupled to spectroscopy to obtain chemical information through changes in the localized surface plasmon resonance. [43][44][45] Interferometric configuration allows increasing the OPT signal to background ratio, as in the interferometric scattering microscope (iSCAT), but it cannot apply to electrochemistry since it relies on reflections at an insulating interface. 46,47 However, recent works have shown that ultrathin layer of absorbing and conducting materials deposited onto a glass substrate could be used in an interferometric observation mode named BALM for backside absorbing layer microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Dark-field microscopy is also frequently coupled to spectroscopy to obtain chemical information through changes in the localized surface plasmon resonance. [43][44][45] Interferometric configuration allows increasing the OPT signal to background ratio, as in the interferometric scattering microscope (iSCAT), but it cannot apply to electrochemistry since it relies on reflections at an insulating interface. 46,47 However, recent works have shown that ultrathin layer of absorbing and conducting materials deposited onto a glass substrate could be used in an interferometric observation mode named BALM for backside absorbing layer microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Color camera or hyperspectral dark field microscopes, e.g. via commercial platform (Cytoviva®, [60][61][62][63]) or hyperspectral camera, collect images with both full spectral identification and 2D localization of single NPs.…”
Section: [322] Dark-field Microscopymentioning
confidence: 99%
“…The surface plasmon resonance peak position depends on a number of factors including the particle size, shape and agglomeration state [14,52]. Under dark field illumination individual silver nanoparticles as small as 10-15 nm in diameter can be observed under optimal conditions [22,23]. If the dimensions of the nanoparticle are below the wavelength of the light, on a microscope image a single nanoparticle appears as an individual diffraction-limited spot.…”
Section: Optical Measurements Of Scattering From Silver Nanoparticlesmentioning
confidence: 99%
“…Metallic nanoparticles are visible using a dark-field optical microscope within a wide size limit between ca. 10 and 100 nm in diameter [22,23] and under suitable conditions individual particles or their clusters can be separately monitored [24]. This is in contrast to many other experimental techniques which are often limited to measuring the average response across a nanoparticle population.…”
Section: Introductionmentioning
confidence: 99%